Business relationships for competitive advantage : (Palgrave Macmillan, 2004)
Buyers seek to manage suppliers and sellers look for good customers, but how can buyers and sellers align their relationships effectively? This new book provides an overview of the dominant schools of thought concerning ways that buyers and sellers can manage their relationships appropriately. These include purchasing portfolio analysis, transaction cost economics, lean and agile supply chain management, customer account management and the resource-based school. The authors reject each of these schools as one-dimensional and advocate instead a holistic approach grounded in the IMP, Power and Relationships Portfolio Mapping approaches. A number of case studies demonstrate how business relationships can be aligned appropriately and inappropriately using this new approach